Usage of urban green space and related feelings of deprivation during the COVID-19 lockdown: Lessons learned from an Italian case study. (June 2021) - Ugolini, Francesca; Massetti, Luciano; Pearlmutter, David; Sanesi, Giovanni
Abstract: This study investigated perceptions and behavioral patterns related to urban green space (UGS) in Italian cities, during the period of national lockdown imposed due to the outbreak of SARS-CoV-2 in the spring of 2020. A survey was used to examine the responses of population groups in different municipal areas, comparing those in government-defined "red zones", mostly in the northern regions of the country, with "non-red zones" in the rest of the country, where the rate of infection was much lower. A total of 2100 respondents participated in the survey. The majority of respondents declared themselves to be habitual users of UGS, especially of parks or green areas outside the town – mainly visiting for relaxation and physical exercise, but also for observing nature. In the northern regions people more commonly reported the adoption of sustainable practices, in terms of the utilization of tools for "green mobility". During the lockdown, habits changed significantly: only one third of respondents reported visiting UGS, with frequent visits made mainly for the purpose of walking the dog. Other motivations included the need for relaxing, mostly in the red zones, and for physical exercise in non-red zones. The reduction in travel to urban parks was accompanied by increased visitation of gardens and other green spaces in close proximity, as social distancing and other regulations imposed restrictions on movement. In all regions, respondents who could not physically access UGS expressed a feeling of deprivation which was exacerbated by living in towns located in red zones, being a usual visitor of UGS and having no green view from the window. The extent to which these visitors missed UGS depended on the frequency of visitation before the pandemic and the UGS distance, as well as the type of previous activity. In fact, those activities that were most common before the pandemic were missed the most, reinforcing the importance of green areas for social gathering, sports, and observing nature – but simply "spending time outdoors" was also mentioned, even by those who visited UGS during the lockdown, as the time outdoors was not enough or not fully enjoyed. The feeling of missing UGS was only partially alleviated by the green view from the window – only a more open view to a natural landscape or adaptation to a view with little greenery reduced such feeling. Highlights: The outbreak of SARS-CoV-2 induced a change in UGS visitation for essential motivations. The feeling of UGS deprivation was accentuated for those with some view of greenery. Respondents demonstrated heightened awareness of the importance of respect for nature. Respondents suggested urban policies addressing sustainability and resilience goals for cities. Respondents suggested UGS expansion, improvement and pocket-greenery within neighborhoods.